Efecto de los criterios de autolimpieza en el diseño optimizado de redes de alcantarillado : aplicación de metodología en el caso de Bogotá (2017)
This research aimed to evaluate the effect of self-cleansing criteria on the design and operation of sewage systems. To accomplish this objective, a series of graphs and tools were developed in order to evaluate real networks in the city of Bogotá. Using the information from the SIMA-P, a tool developed by the aqueduct company of Bogotá, different areas of the city were selected for later evaluation. In this research, initially several UGAs were analyzed, using only topological information of the networks; in addition, two hydraulic models were analyzed under different scenarios to deepen the investigation. These analyzes allowed to conclude that self-cleansing criteria are more relevant in the design of sanitary sewer systems than in the design of storm water systems. Also it was possible to establish that in the operation of this kind of systems there could be external factors that can cause sedimentation and obstructions in the system?s pipes; so, in addition to fulfilling the different self-cleansing restrictions, it is necessary to have operation and preventive maintenance plans for the proper operation of the sewerage systems.